Whole-core forward-adjoint neutron transport solutions with coupled 2-D MOC and 1-D SN and kinetics parameter calculation. (September 2018) - Wu, Qu; Peng, Xingjie; Tang, Xiao; Yu, Yingrui; Li, Qing; Wang, Kan
Abstract: The 2-D/1D whole-core transport method has been widely studied for 3-D fine flux or power distributions and implemented in many deterministic codes. KYCORE, a 2-D/1-D transport code, developed a new iteration strategy to calculate forward flux. In order to perform kinetics parameter computation and sensitivity analysis, an adjoint flux solution is required in modern reactor physics analysis. In this study, a new adjoint neutron transport solver, named KYADJ, was developed by utilizing the 2-D MOC and 1-D SN coupling method. A 3 × 3 lattice test problem and C5G7 OECD/NEA 3-D benchmarks were used to verify the forward-adjoint neutron transport calculation of KYADJ. Forward-adjoint multiplication factors, forward flux, adjoint flux and kinetics parameters were compared with reference results generated by the Reactor Monte Carlo code RMC. Results showed that KYADJ agreed well with RMC and KYADJ had the ability to provide fine pin-by-pin forward and adjoint flux distributions and accurately compute kinetics parameters.